1995
DOI: 10.1016/s0042-6822(95)80044-1
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the bean strain of southern bean mosaic virus

Abstract: The genome of the bean strain of southern bean mosaic virus (SBMV-B) comprises 4109 nucleotides and thus is slightly shorter than those of the two other sequenced sobemoviruses (southern bean mosaic virus, cowpea strain (SBMV-C) and rice yellow mottle virus (RYMV)). SBMV-B has an overall sequence similarity with SBMV-C of 55% and with RYMV of 45%. Three potential open reading frames (ORFs) were recognized in SBMV-B which were in similar positions in the genomes of SBMV-C and RYMV. However, there was no analog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
10

Year Published

1997
1997
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 56 publications
0
20
0
10
Order By: Relevance
“…None of the clones sequenced had the terminal 5 sequence of the SeMV RNA. A comparison of the 5 terminal 51 nts of pSM63 with SBMV [19] showed that it was identical from nts 14 to 64 (Fig. 2).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…None of the clones sequenced had the terminal 5 sequence of the SeMV RNA. A comparison of the 5 terminal 51 nts of pSM63 with SBMV [19] showed that it was identical from nts 14 to 64 (Fig. 2).…”
Section: Resultsmentioning
confidence: 92%
“…It is 15 and 45 nts longer than SBMV-Ark and SBMV [13,19] genomic RNAs and 47 nts shorter than SCPMV genomic RNA [32]. Four potential overlapping ORFs were identified from the messenger sense strand and no ORFs coding greater than 85 amino acids were identified on the negative sense strand.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations